PEMBENTUKAN BUDI PEKERTI YANG BAIK MELALUI SISTEM AMONG PADA PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN - Yesni Yesni; Sudjarwo Sudjarwo; Irawan Suntoro (Faculty of Teacher Training and Education, University of Lampung, 2013)
This study aims to find out : (1) planning learning to use the system in the formation of character among the learning citizenship education in SMA N I Way Tuba Way Kanan. (2) Implementation of the system among the establishment of good behaviour on Lesson PKn in SMA N I Way Tuba Way Kanan. (3) Evaluating students’ attitudes toward learning among systems in the formation of character on learning the citizenship education tauhgt in SMA N I Way Tuba Way Kanan.The method used was Classroom Action Research Methods. From the results of the actions that : In the first cycle of activity obtained amounting 60% the category is quite, then at the second cycle amounting 75% good category and the third cycle amounting 88% the category of very good. Based on the above results, it can be seen that the abilitiy of teachers to use the method in improving system among character on learning Civics have achieved satisfactory results,with the number of changes in behavior and character of students.Keywords : Method of Citizenship Education learning among systems can from a good character on the system.